2018
DOI: 10.1021/acs.chemmater.8b00290
|View full text |Cite
|
Sign up to set email alerts
|

Triphenyl Phosphite as the Phosphorus Source for the Scalable and Cost-Effective Production of Transition Metal Phosphides

Abstract: Transition metal phosphides have great potential to optimize a number of functionalities in several energy conversion and storage applications, particularly when nanostructured or in nanoparticle form. However, the synthesis of transition metal phosphide nanoparticles and its scalability is often limited by the toxicity, air sensitivity and high cost of the reagents used. We present here a simple, scalable and cost-effective 'heating up' procedure to produce metal phosphides using inexpensive, lowtoxicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 77 publications
5
92
0
Order By: Relevance
“…After heat treatment at 300 °C (P1‐V 2 CT x ), it shows the visible peaks of P 2p, which is assigned to be PO 133.5 eV (P 2p 3/2 ), 134.4 eV (P 2p 1/2 ), and very little peak of PC at 130.5 eV (P 2p 3/2 ), 132.1 eV (P 2p 1/2 ) . In previous results for synthesizing the transition metal phosphide (Ni, Co, and Fe), they used to perform the reaction at above 300 °C . However, it is confirmed that reactivity of V 2 CT x to phosphine (PH 3 ) is low at 300 °C, as only the PO (phosphorous oxide) prominently appears, while there is a peak of PC with small intensity, which means that P‐oxide is formed easily by oxidation or decomposition of TPP at 300 °C rather than formation of chemical doping states.…”
Section: Resultsmentioning
confidence: 99%
“…After heat treatment at 300 °C (P1‐V 2 CT x ), it shows the visible peaks of P 2p, which is assigned to be PO 133.5 eV (P 2p 3/2 ), 134.4 eV (P 2p 1/2 ), and very little peak of PC at 130.5 eV (P 2p 3/2 ), 132.1 eV (P 2p 1/2 ) . In previous results for synthesizing the transition metal phosphide (Ni, Co, and Fe), they used to perform the reaction at above 300 °C . However, it is confirmed that reactivity of V 2 CT x to phosphine (PH 3 ) is low at 300 °C, as only the PO (phosphorous oxide) prominently appears, while there is a peak of PC with small intensity, which means that P‐oxide is formed easily by oxidation or decomposition of TPP at 300 °C rather than formation of chemical doping states.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] The binary Ni-P phase diagram is complex, with a large number of thermodynamically stable stoichiometries (Ni 3 P, Ni 5 P 2 , Ni 12 P 5 , Ni 2 P, Ni 5 P 4 , NiP, NiP 2 , and NiP 3 ), thereby creating a synthetic challenge with respect to accessing phase-pure Ni 2 P. In general, increasing the molar equivalents of phosphide precursor, extending the reaction time, and operating at higher temperatures allow the more phosphorus-rich side of the phase diagram to be accessed for colloidal nanocrystals. [12][13][14] Typical methods used to synthesize high-quality colloidal Ni 2 P nanocrystals use traditional organic solvents (e.g., octadecene (ODE), dioctyl ether), expensive and/or reactive phosphide precursors (tri-n-octylphosphine (TOP), white phosphorus (P 4 ), tris(trimethylsilyl)phosphine (P(TMS) 3 ), and tri-n-butylphosphine), high temperatures, and/or multiple-step reactions. 10,[15][16][17] Triphenylphosphine (PPh 3 ) is a low-cost, less-reactive, and more air-stable phosphide precursor (~15% the cost of TOP in price per mole); 18 however, compared to TOP and P(TMS) 3 , nanocrystals synthesized using PPh 3 are typically large (>45 nm), ill-defined, amorphous, and/or not phase pure.…”
mentioning
confidence: 99%
“…[28] The P atoms neighboring the vacancies continue to react with DMF molecules according to Equation (2). Afterwards, the growth of the 2D TMPs involves two steps: [29] First, reduction of the metal ions to the metal (M) at hydrogenated P vacancies [Eq. (3)] followed by phosphidation of the metal clusters at the phosphorene interfaces…”
Section: Resultsmentioning
confidence: 99%